Bushpig (Potamochoerus larvatus) Hunting in Rural Areas of Madagascar and Its Health and Socioeconomic Implications - Rakotoarivony, Rianja; Molia, Sophie; Rakotomalala, Eric; Ramy-Ratiarison, Ranto; Jori, Ferran; Pedrono, Miguel (Frontiers in Conservation Science, 2022)
Bushmeat consumption and trade plays a relevant role in many tropical countries as a source of protein and income for rural populations. In Madagascar, rural populations depend heavily on natural resources and wildlife as source of income and protein. The bushpig (Potamochoerus larvatus) is the largest mammal available in the island and regularly hunted. However, little is known about the importance and characteristics of this activity and its implication as a potential source of pathogens for both humans and domestic animals. A cross-sectional study was conducted in 2014–2015 in five different regions of rural Madagascar suspected to have significant bushpig populations to (i) quantify and characterize the importance of bushpig hunting, (ii) assess the socioeconomic impact of bushpig trade, (iii) evaluate the potential pathogen transmission between bushpigs, domestic pigs and humans. A total of 77 hunters, 10 butchers and 95 pig farmers were individually interviewed. Hunting seasonality and the perception of local hunters with regards to the dynamics of bushpig populations in the last decade differed between the tropical dry and tropical sub-arid climatic zones. The top reason for hunting bushpigs was crop protection but personal consumption and selling of meat were also common. Hunting efficacy was largely dependent on the technique used. Snares and traps, the most widely used techniques, allowed the majority of hunters to catch from one to 10 bushpigs per year. Limited commercial bushpig trade was observed with only 0.8 bushpig sold in average per year and per hunter, representing a 16 USD income. The average price per kilo sold was USD 0.8 and the average profit received by each butcher/collector after the sale of a carcass was USD 11.9. No perception of disease risks nor precautions were taken to prevent potential pathogen transmission from bushpig to humans or pigs. Most of the hunters (68%) indicated that they had never seen a diseased bushpig. Bushpig hunting in our study areas in Madagascar was basically a small-scale subsistence hunting, very different from commercial bushmeat hunting described in areas of Central Africa or the Amazon Basin. More research is needed to verify the sustainability of bushpig hunting and its potential role in terms of reducing pressure on other endemic wildlife species and transmitting pathogens to humans and pigs.